Training Module: Gender Responsive Digital Inclusion - Ravula, Padmaja; Rupavatharam, Srikanth; Kasala, Kavitha; Kumar, Kishore; Singaraju, Niyathi (2024)
This Training Manual on “Gender responsive digital inclusion” is developed to provide basic training/workshops on gender concepts, digital gender divides and mainstreaming tools, frameworks, etc. This manual is designed for Gender Focal Persons (GFPs) to conduct basic gender training/ workshops/sensitization within their sectors. It can also be used to train new GFPs and conduct refresher courses for the existing GFPs. Although the definitions and understanding of gender concepts are drawn from the standard international definitions, the manual has tried to, wherever possible, contextualize using local case studies, group exercises and materials. Highlighted to use of local case studies, examples and audiovisual materials is also intended to create awareness on the gender issues at hand within the country. This manual consists of 8 modules/handouts. Each module/handout is by facilitator notes, PowerPoint presentations, case studies and instruction for group work including the approximate time duration to conduct every module. The modules are also arranged sequentially; however, the users of this manual may choose to pick relevant modules for their own sector or target audience depending on time available. The facilitators may also use case studies that may be more relevant for their sector or target audience than those given in the manual and could have the flexibility to improve and adjust the group activities as may be deemed most effective. This manual may not be as comprehensive, but it is expected that this would create a spark and encourage users to delve deeper into the field of gender and digital studies. The manual will be a living document, which will be periodically updated depending on the need. Hence, any feedback or suggestions are encouraged from users of this manual.